ZEB1 Mediates Bone Marrow Mesenchymal Stem Cell Osteogenic Differentiation Partly via Wnt/β-Catenin Signaling - Xu, Cuidi; Shi, Hongli; Jiang, Xin; Fan, Yongqian; Huang, Donghui; Qi, Xinming; Cheng, Qun (Frontiers in Molecular Biosciences, 2021)
Zinc finger E-box-binding homebox 1 (ZEB1) is a zinc-finger transcription factor best known for its role in promoting the epithelial-mesenchymal transition, which is also related to osteogenesis. Here, ZEB1 was investigated for its role in the commitment of bone marrow mesenchymal stem cells (BMSCs) to osteoblasts. In vitro, ZEB1 expression decreased following osteogenic differentiation. Furthermore, silencing of ZEB1 in BMSCs promoted osteogenic activity and mineralization. The increase in osteogenic differentiation induced by si-ZEB1 could be partly rescued by the inhibition of Wnt/β-catenin (si-β-catenin). In vivo, knockdown of ZEB1 in BMSCs inhibited the rapid bone loss of ovariectomized (OVX) mice. ZEB1 expression has also been negatively associated with bone mass and bone formation in postmenopausal women. In conclusion, ZEB1 is an essential transcription factor in BMSC differentiation and may serve as a potential anabolic strategy for treating and preventing postmenopausal osteoporosis (PMOP).